From TikTok to Truth Social: a data analysis of Gen Z’s platform preferences following the 2024 election - Wagner, Dawson (My University, 2025)
As social media continues to shape political discourse, Generation Z has emerged as a distinct and influential demographic in U.S. elections. This study explores Gen Z’s social media platform usage during the 2024 presidential election and investigates how their political affiliation, gender, and opinions of platform owners relate to their usage habits and concern about misinformation. Using a quantitative approach, original survey data was collected from 188 Gen Z respondents at Kansas State University. Descriptive statistics and paired samples t-tests were conducted to compare usage frequency across platforms such as TikTok, Instagram, Snapchat, and Facebook. Independent samples t-tests and bivariate correlations were used to assess differences in usage patterns by vote choice, political ideology, and gender. Results show that TikTok, Instagram, Snapchat, and YouTube were the most frequently used platforms, while Facebook, X (formerly Twitter), and emerging platforms like Truth Social and Threads had significantly lower engagement. Liberal-leaning participants reported lower favorability toward platform owners like Elon Musk and Donald Trump, while platform usage varied significantly across gender and political lines. These findings provide insight into the digital behaviors and values that guided Gen Z’s media choices in the 2024 election and contribute to a growing understanding of how this generation navigates political information in a fragmented and polarized online ecosystem.
Keywords: Gen Z; Social media usage; Political communication; Misinformation; Platform trust; Tech ownership